Answer:
Use Desmos.com/calculator
Step-by-step explanation:
Remember, y=mx+b
y is equal to any given y point
x is equal to any given x point
m is equal to slope
b is equal to the y-intercept, or where x = 0 and the line crosses the horizon line.
In order to graph the line correctly, you have to isolate y.
y+x=-3
y=-x-3 would be equal to y=mx+b format
slope is negative 1
y intercept is negative 3
start on the y line, go to (0,-3) and start your line.
slope is negative 1, so you go down one and right one.
Answer:
The slope is "Undefined"
Step-by-step explanation:
Answer:
It gains a slope of 5 over 1
Step-by-step explanation:
10000:100*11=1100 income per year
21000-10000=11000 need to have income
11000:1100=10 years will pass time
Answer:
a. ![\mathbf{Y(s) = L \{y(t)\} = \dfrac{7}{s(s+1)}+ \dfrac{e^{-3s}}{s+1}}](https://tex.z-dn.net/?f=%5Cmathbf%7BY%28s%29%20%3D%20L%20%5C%7By%28t%29%5C%7D%20%3D%20%5Cdfrac%7B7%7D%7Bs%28s%2B1%29%7D%2B%20%5Cdfrac%7Be%5E%7B-3s%7D%7D%7Bs%2B1%7D%7D)
b. ![\mathbf{y(t) = \{7e^t + e^3 u (t-3)-7\}e^{-t}}](https://tex.z-dn.net/?f=%5Cmathbf%7By%28t%29%20%3D%20%5C%7B7e%5Et%20%2B%20e%5E3%20u%20%28t-3%29-7%5C%7De%5E%7B-t%7D%7D)
Step-by-step explanation:
The initial value problem is given as:
![y' +y = 7+\delta (t-3) \\ \\ y(0)=0](https://tex.z-dn.net/?f=y%27%20%2By%20%3D%207%2B%5Cdelta%20%28t-3%29%20%5C%5C%20%5C%5C%20y%280%29%3D0)
Applying laplace transformation on the expression ![y' +y = 7+\delta (t-3)](https://tex.z-dn.net/?f=y%27%20%2By%20%3D%207%2B%5Cdelta%20%28t-3%29)
to get ![L[{y+y'} ]= L[{7 + \delta (t-3)}]](https://tex.z-dn.net/?f=L%5B%7By%2By%27%7D%20%5D%3D%20L%5B%7B7%20%2B%20%5Cdelta%20%28t-3%29%7D%5D)
![l\{y' \} + L \{y\} = L \{7\} + L \{ \delta (t-3\} \\ \\ sY(s) -y(0) +Y(s) = \dfrac{7}{s}+ e ^{-3s} \\ \\ (s+1) Y(s) -0 = \dfrac{7}{s}+ e^{-3s} \\ \\ \mathbf{Y(s) = L \{y(t)\} = \dfrac{7}{s(s+1)}+ \dfrac{e^{-3s}}{s+1}}](https://tex.z-dn.net/?f=l%5C%7By%27%20%5C%7D%20%2B%20L%20%5C%7By%5C%7D%20%3D%20L%20%5C%7B7%5C%7D%20%2B%20L%20%5C%7B%20%5Cdelta%20%28t-3%5C%7D%20%5C%5C%20%5C%5C%20sY%28s%29%20-y%280%29%20%2BY%28s%29%20%3D%20%5Cdfrac%7B7%7D%7Bs%7D%2B%20e%20%5E%7B-3s%7D%20%5C%5C%20%5C%5C%20%28s%2B1%29%20Y%28s%29%20-0%20%3D%20%5Cdfrac%7B7%7D%7Bs%7D%2B%20e%5E%7B-3s%7D%20%5C%5C%20%5C%5C%20%5Cmathbf%7BY%28s%29%20%3D%20L%20%5C%7By%28t%29%5C%7D%20%3D%20%5Cdfrac%7B7%7D%7Bs%28s%2B1%29%7D%2B%20%5Cdfrac%7Be%5E%7B-3s%7D%7D%7Bs%2B1%7D%7D)
Taking inverse of Laplace transformation
![y(t) = 7 L^{-1} [ \dfrac{1}{(s+1)}] + L^{-1} [\dfrac{e^{-3s}}{s+1}] \\ \\ y(t) = 7L^{-1} [\dfrac{(s+1)-s}{s(s+1)}] +L^{-1} [\dfrac{e^{-3s}}{s+1}] \\ \\ y(t) = 7L^{-1} [\dfrac{1}{s}-\dfrac{1}{s+1}] + L^{-1}[\dfrac{e^{-3s}}{s+1}] \\ \\ y(t) = 7 [1-e^{-t} ] + L^{-1} [\dfrac{e^{-3s}}{s+1}]](https://tex.z-dn.net/?f=y%28t%29%20%3D%207%20L%5E%7B-1%7D%20%5B%20%5Cdfrac%7B1%7D%7B%28s%2B1%29%7D%5D%20%2B%20L%5E%7B-1%7D%20%5B%5Cdfrac%7Be%5E%7B-3s%7D%7D%7Bs%2B1%7D%5D%20%5C%5C%20%5C%5C%20y%28t%29%20%3D%207L%5E%7B-1%7D%20%5B%5Cdfrac%7B%28s%2B1%29-s%7D%7Bs%28s%2B1%29%7D%5D%20%2BL%5E%7B-1%7D%20%5B%5Cdfrac%7Be%5E%7B-3s%7D%7D%7Bs%2B1%7D%5D%20%5C%5C%20%5C%5C%20y%28t%29%20%3D%207L%5E%7B-1%7D%20%5B%5Cdfrac%7B1%7D%7Bs%7D-%5Cdfrac%7B1%7D%7Bs%2B1%7D%5D%20%2B%20L%5E%7B-1%7D%5B%5Cdfrac%7Be%5E%7B-3s%7D%7D%7Bs%2B1%7D%5D%20%5C%5C%20%5C%5C%20y%28t%29%20%3D%207%20%5B1-e%5E%7B-t%7D%20%5D%20%2B%20L%5E%7B-1%7D%20%5B%5Cdfrac%7Be%5E%7B-3s%7D%7D%7Bs%2B1%7D%5D)
![L^{-1}[\dfrac{e^{-3s}}{s+1}]](https://tex.z-dn.net/?f=L%5E%7B-1%7D%5B%5Cdfrac%7Be%5E%7B-3s%7D%7D%7Bs%2B1%7D%5D)
![L^{-1}[\dfrac{1}{s+1}] = e^{-t} = f(t) \ then \ by \ second \ shifting \ theorem;](https://tex.z-dn.net/?f=L%5E%7B-1%7D%5B%5Cdfrac%7B1%7D%7Bs%2B1%7D%5D%20%3D%20e%5E%7B-t%7D%20%20%3D%20f%28t%29%20%5C%20then%20%5C%20by%20%5C%20second%20%5C%20shifting%20%5C%20theorem%3B)
![L^{-1}[\dfrac{e^{-3s}}{s+1}] = \left \{ {{f(t-3) \ \ \ t>3} \atop {0 \ \ \ \ \ \ \ \ \ t](https://tex.z-dn.net/?f=L%5E%7B-1%7D%5B%5Cdfrac%7Be%5E%7B-3s%7D%7D%7Bs%2B1%7D%5D%20%3D%20%5Cleft%20%5C%7B%20%7B%7Bf%28t-3%29%20%5C%20%5C%20%5C%20t%3E3%7D%20%5Catop%20%7B0%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%20%5C%20%5C%20%20%5C%20t%20%3C3%7D%7D%20%5C%20%5C%20%5C%20%20%5Cright.)
![L^{-1}[\dfrac{e^{-3s}}{s+1}] = \left \{ {{e^{(-t-3)} \ \ \ t>3} \atop {0 \ \ \ \ \ \ \ \ \ t](https://tex.z-dn.net/?f=L%5E%7B-1%7D%5B%5Cdfrac%7Be%5E%7B-3s%7D%7D%7Bs%2B1%7D%5D%20%3D%20%5Cleft%20%5C%7B%20%7B%7Be%5E%7B%28-t-3%29%7D%20%5C%20%5C%20%5C%20t%3E3%7D%20%5Catop%20%7B0%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%20%5C%20%5C%20%20%5C%20t%20%3C3%7D%7D%20%5C%20%5C%20%5C%20%20%5Cright.)
![= e^{-t-3} \left \{ {{1 \ \ \ \ \ t>3} \atop {0 \ \ \ \ \ t](https://tex.z-dn.net/?f=%3D%20e%5E%7B-t-3%7D%20%5Cleft%20%5C%7B%20%7B%7B1%20%5C%20%5C%20%5C%20%5C%20%5C%20%20t%3E3%7D%20%5Catop%20%7B0%20%5C%20%5C%20%5C%20%5C%20%5C%20%20t%3C3%7D%7D%20%5Cright.)
= ![e^{-(t-3)} u (t-3)](https://tex.z-dn.net/?f=e%5E%7B-%28t-3%29%7D%20u%20%28t-3%29)
Recall that:
![y(t) = 7 [1-e^{-t} ] + L^{-1} [\dfrac{e^{-3s}}{s+1}]](https://tex.z-dn.net/?f=y%28t%29%20%3D%207%20%5B1-e%5E%7B-t%7D%20%5D%20%2B%20L%5E%7B-1%7D%20%5B%5Cdfrac%7Be%5E%7B-3s%7D%7D%7Bs%2B1%7D%5D)
Then
![y(t) = 7 -7e^{-t} +e^{-(t-3)} u (t-3)](https://tex.z-dn.net/?f=y%28t%29%20%3D%207%20-7e%5E%7B-t%7D%20%20%2Be%5E%7B-%28t-3%29%7D%20u%20%28t-3%29)
![y(t) = 7 -7e^{-t} +e^{-t} e^{-3} u (t-3)](https://tex.z-dn.net/?f=y%28t%29%20%3D%207%20-7e%5E%7B-t%7D%20%20%2Be%5E%7B-t%7D%20e%5E%7B-3%7D%20u%20%28t-3%29)
![\mathbf{y(t) = \{7e^t + e^3 u (t-3)-7\}e^{-t}}](https://tex.z-dn.net/?f=%5Cmathbf%7By%28t%29%20%3D%20%5C%7B7e%5Et%20%2B%20e%5E3%20u%20%28t-3%29-7%5C%7De%5E%7B-t%7D%7D)